2021
DOI: 10.1108/ijse-10-2020-0718
|View full text |Cite
|
Sign up to set email alerts
|

Are we all in this together? Alleviating the childcare constraint for women in economic crises

Abstract: PurposeThe purpose of the paper is to advocates the use of gendered economic policies to stimulate a post-COVID-19 recovery. It alerts on the risk of ignoring the female dimension of the current crisis and of resorting again to austerity programs that, like the ones enacted after the 2008 crisis, would hit women and mothers disproportionally harder than other groups.Design/methodology/approachThe authors use data from the British Household Panel Survey on female participation and account for gendered constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Policies oriented to alleviate childcare constraints can be sustainable and effective in encouraging women back to work. Considering factors wider than the standard economic variables when designing labor market policies can yield tangible results in terms of increasing women's workforce participation (Cagliesi & Hawkes, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Policies oriented to alleviate childcare constraints can be sustainable and effective in encouraging women back to work. Considering factors wider than the standard economic variables when designing labor market policies can yield tangible results in terms of increasing women's workforce participation (Cagliesi & Hawkes, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies also suggest that women, in general, bear the brunt of child and family care (Cagliesi & Hawkes, 2021). These studies reported that mothers reduced their working hours compared to their male counterparts.…”
Section: Model and Hypothesesmentioning
confidence: 99%
“…An integrated questionnaire was used to collect the data. Extant research by scholars such asCagliesi and Hawkes (2021),Cheche et al (2019) andDas et al (2021) suggests the influence of specific demographic variables on the constructs in use. Based on their submissions, the following demographic data were collected: marital status, gender, level of work, parenting and age.…”
mentioning
confidence: 99%